PENGARUH PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI MEDIA PEMBELAJARAN TERHADAP PEMAHAMAN SISWA TENTANG BENDA PADAT DAN CAIR DI KELAS 2 SDN BURNEH 1 BANGKALAN - Yuliatin, Suryani; Kusuma, Rendra Sakbana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of using the surrounding environment as a learning medium on students' understanding of solid and liquid objects in class 2 of SDN Burneh 1 Bangkalan. The type of research used in this research is quantitative research. The number of subjects in the research was 20 grade 2 students at SDN Burneh 1 Bangkalan. By using the test question data collection method. The data used in this research are validity test, reliability test, normality test and paired sample t-test. With the results of the t test on the paired sample t-test on cokom siqnification of 0.000<0.05 based on the results of this analysis it can be interpreted that the pretest and posttest scores experienced significant changes, namely that there was an influence of the use of the surrounding environment as a learning medium on students' understanding of objects. solid and liquid in class 2 burneh 1 elementary school Bangkalan.